Antibacterial chinlon slice and preparation method thereof
The silver-loaded antibacterial agent is prepared by modifying Ag nanoparticles by amidated chitosan and melt blended with nylon slices, which solves the problem of nylon fiber color discoloration, improves its antibacterial and color discoloration resistance, and achieves the stability of color and performance sex.
Patent Information
- Application Number
- CN202411138291.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
Nylon fibers are prone to discoloration during processing and use, resulting in poor antibacterial properties. Especially in high temperature and high humidity environments, silver ions precipitate to form colored compounds, affecting the fiber color stability.
Ag nanoparticles are modified by amidated chitosan, silver-loaded antibacterial agent is prepared, and melt-blended with nylon slices, and then cooled to form antibacterial nylon slices, enhancing antibacterial properties and improving the stability of silver ions in fibers.
It improves the antibacterial and discoloration resistance of nylon fibers, ensuring the color stability and antibacterial effect of the fibers in high temperature and high humidity environments.
Smart Images

Figure BDA0005000015010000061 
Figure BDA0005000015010000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textiles, and in particular relates to an antibacterial nylon slice and a preparation method thereof. Background Art
[0002] With the rapid development of the global economy, the technology and product quality of the nylon chips industry are constantly improving. Nylon chips have become an important branch of the synthetic chemical materials industry, with extremely wide application areas, and are used in the textile industry to prepare nylon fibers.
[0003] As people pay more attention to health, they also put forward antibacterial functional requirements for textiles. The antibacterial effect of textiles is mainly achieved by antibacterial fibers. Silver ion antibacterial agents are very efficient antibacterial agents and are very safe for the human body. They are widely used in the production of antibacterial fibers. Nylon fiber is the second largest fiber in chemical fiber production after polyester. It has good hygroscopicity and good affinity with the human body. It is used in underwear, swimsuits, socks, ribbons, etc. Silver ion antibacterial agents are also used in nylon fibers.
[0004] However, nylon fibers that use silver ion antimicrobial agents are very prone to discoloration during processing and use. When the fiber is left for too long or the acidity and alkalinity of the environment changes, it will produce red, brown and other color changes, and the fabric will produce uneven color spots and blocks, which seriously affects the use of antimicrobial nylon fibers. The main reason for the discoloration is that the silver ions in the loaded antimicrobial agent precipitate too quickly, especially in a high temperature and high humidity environment, the precipitated silver ions generate colored compounds, causing the fiber or fabric color to change. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide an antibacterial nylon slice and a preparation method thereof, so as to solve the technical problems of poor antibacterial property and easy discoloration of nylon fiber.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing an antibacterial nylon slice, characterized in that it is prepared by the following steps:
[0008] S1, amidation modification of chitosan using methyl acrylate and amino-terminated polyether to obtain amidated chitosan PMCS;
[0009] S2, using amidated chitosan PMCS to modify Ag nanoparticles to obtain silver ion-carrying antibacterial agent PMCS-Ag;
[0010] S3, melt-blending the silver ion antibacterial agent PMCS-Ag with the nylon slices, and slicing them after cooling to obtain the antibacterial nylon slices.
[0011] Furthermore, the step of amidation modification of chitosan using methyl acrylate and amino-terminated polyether in S1 is:
[0012] S11, chitosan and methyl acrylate undergo Michael addition reaction: chitosan powder is added to a methanol solution, and the mixture is continuously stirred until the chitosan powder is completely dispersed in the methanol solution; methyl acrylate is added to the solution, and the solution is stirred at 50-60° C. for 20-24 hours, and then centrifuged and washed to obtain a precipitate;
[0013] S12, preparing amino-terminated polyether: mixing adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG, 2 The temperature is raised to 170-180° C. under protection, and kept warm for 30-60 minutes; 2-3% of the total amount of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG is added with phosphorous acid as an antioxidant, and the temperature is raised to 220-260° C. for polycondensation reaction for 1.5-3.5 hours to obtain amino-terminated polyether;
[0014] S13, the terminal ester group of chitosan undergoes an amidation reaction with the amino-terminated polyether: the precipitate in S11 is added to a methanol solution, and the stirring is continued until the precipitate is completely dispersed in the methanol solution; the amino-terminated polyether is added to the methanol solution, and the solution is stirred at 50-60° C. for 20-24 hours, and then centrifuged and washed to obtain amidated chitosan PMCS.
[0015] Furthermore, the ratio of chitosan powder to methyl acrylate in the S11 is 3-5 g: 0.5-1.0 mL.
[0016] Furthermore, the weight ratio of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG in S12 is 0.6-1.2:3:1;
[0017] The molecular weight of double-terminated carboxyl polyethylene glycol CT-PEG is 1000.
[0018] Furthermore, the ratio of the precipitate in S13 to the amino-terminated polyether is 3-5 g: 1-2 mL.
[0019] Furthermore, the step of modifying Ag nanoparticles with amidated chitosan PMCS in S2 is as follows: taking amidated chitosan PMCS powder, adding it into distilled water and adding glacial acetic acid to adjust the pH value to 3-4, so that PMCS is completely dissolved; then adding AgNO 3 solution, stir to mix; then add the freshly prepared NaBH 4solution, stirring the reaction for 10-15 minutes; adding ammonia water to adjust the pH value to alkaline so that precipitation appears in the solution, centrifuging the solution to obtain solid matter, washing the solid matter with distilled water, washing with acetone, and drying at room temperature for 10-12 hours to obtain the silver ion-carrying antibacterial agent PMCS-Ag.
[0020] Furthermore, the PMCS, AgNO 3 Solution and NaBH 4 The dosage ratio of the solution is 0.05-0.1g: 1-10mL: 0.5-1mL; AgNO 3 The concentration of the solution is 10mmol / L, NaBH 4 The concentration of the solution is 100mmol / L.
[0021] Furthermore, the silver ion antibacterial agent PMCS-Ag in S3 accounts for 1-10% of the mass of the nylon slice;
[0022] The temperature of melt blending is 180-220°C.
[0023] An antibacterial nylon slice is prepared by the preparation method.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention uses amidated chitosan to modify Ag nanoparticles to obtain a silver ion-loaded antibacterial agent, and the antibacterial properties of the silver ion antibacterial agent are enhanced by combining chitosan with silver ions, so that the nylon fiber prepared by melt spinning the antibacterial nylon slice has excellent antibacterial properties.
[0026] (2) The present invention uses amidated chitosan to modify Ag nanoparticles. The amidated chitosan can improve the compatibility of silver ion antibacterial agents with nylon, and at the same time can protect the silver ions to exist stably in nylon and not easily precipitate, so that the nylon fiber prepared by melt spinning of the antibacterial nylon slices has excellent discoloration resistance. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides an antibacterial nylon slice, which is prepared by the following steps:
[0030] S1. Amidation modification of chitosan using methyl acrylate and amino-terminated polyether:
[0031] S11, chitosan and methyl acrylate undergo Michael addition reaction: 5 g chitosan powder is added to 200 mL methanol solution, and the mixture is stirred continuously until the chitosan powder is completely dispersed in the methanol solution; 1.0 mL methyl acrylate is added to the solution, and the solution is stirred at 50° C. for 24 h, and then centrifuged and washed with methanol to obtain a precipitate;
[0032] S12 Preparation of amino-terminated polyether: Adipic acid AA, hexamethylenediamine HDA and double-carboxyl-terminated polyethylene glycol CT-PEG (molecular weight 1000) were mixed in a weight ratio of 0.6:3:1 and heated to 400 °C in N 2 Under protection, the temperature was raised to 170° C. and kept warm for 30 minutes; an antioxidant phosphorous acid accounting for 3% of the total amount of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG was added, and the temperature was raised to 240° C. for condensation reaction for 2.5 hours to obtain amino-terminated polyether;
[0033] S13, the terminal ester group of chitosan undergoes an amidation reaction with the amino-terminated polyether: 5 g of the precipitate in S11 is added to 200 mL of methanol solution, and the mixture is stirred continuously until the precipitate is completely dispersed in the methanol solution; 2.0 mL of amino-terminated polyether is added to the methanol solution, and the solution is stirred and reacted at 50°C for 24 hours, and then centrifuged and washed with methanol to obtain amidated chitosan PMCS.
[0034] S2. Modification of Ag nanoparticles using amidated chitosan PMCS:
[0035] Take 0.1g amidated chitosan PMCS powder and add it to distilled water. Add glacial acetic acid to adjust the pH to 3-4 to completely dissolve PMCS. Then add 10mL 10mmol / L AgNO 3 The solution was stirred and mixed; then 1 mL of 100 mmol / L freshly prepared NaBH 4 The solution was stirred for reaction for 15 minutes; ammonia water was added to adjust the pH value to alkaline so that precipitation appeared in the solution, and the solution was centrifuged to obtain a solid substance, which was washed with distilled water and acetone and dried at room temperature for 12 hours to obtain a silver ion-carrying antibacterial agent PMCS-Ag.
[0036] S3. Melt-blending the silver ion antibacterial agent PMCS-Ag and nylon slices at 180-220° C., and slicing after cooling to obtain antibacterial nylon slices, wherein the added silver ion antibacterial agent PMCS-Ag accounts for 10% of the mass of the nylon slices.
[0037] Example 2
[0038] Compared with Example 1, this embodiment is different in that “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 0.6:3:1” is changed to “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 0.8:3:1”; the remaining raw materials and preparation process remain the same as in Example 1.
[0039] Example 3
[0040] Compared with Example 1, this embodiment is different in that “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 0.6:3:1” is changed to “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 1.0:3:1”; the remaining raw materials and preparation process remain the same as in Example 1.
[0041] Example 4
[0042] Compared with Example 1, this embodiment is different in that “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 0.6:3:1” is changed to “adipate AA, hexamethylenediamine HDA and double-terminal carboxyl polyethylene glycol CT-PEG (molecular weight 1000) are mixed in a weight ratio of 1.2:3:1”; the remaining raw materials and preparation process remain the same as in Example 1.
[0043] Comparative Example 1
[0044] The difference between this comparative example and Example 1 is that, instead of using amidated chitosan modified Ag nanoparticles as the antibacterial agent, a common silver ion-loaded antibacterial agent, silver-loaded diatomaceous earth, is used as the antibacterial agent, and the other raw materials and preparation process remain the same as those in Example 1.
[0045] Comparative Example 2
[0046] Compared with Example 1, the difference between this comparative example and Example 1 is that the preparation steps of S1 are changed to:
[0047] S11, chitosan and methyl acrylate undergo Michael addition reaction: 5 g chitosan powder is added to 200 mL methanol solution, and the mixture is stirred continuously until the chitosan powder is completely dispersed in the methanol solution; 1.0 mL methyl acrylate is added to the solution, and the solution is stirred at 50° C. for 24 h, and then centrifuged and washed with methanol to obtain a precipitate;
[0048] S12, the terminal ester group of chitosan undergoes an amidation reaction with ethylenediamine: 5 g of the precipitate in S11 is added to 200 mL of methanol solution, and the mixture is stirred continuously until the precipitate is completely dispersed in the methanol solution; 2.0 mL of amino-terminated polyether is added to the methanol solution, and the solution is stirred at 50° C. for 24 h, and then centrifuged and washed with methanol to obtain amidated chitosan PMCS;
[0049] The remaining raw materials and preparation process remain the same as in Example 1.
[0050] The antibacterial nylon slices prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were melt-spun to prepare nylon fibers, and the performance of the nylon fibers was tested. The antibacterial rate of the nylon fibers against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) was detected using the FZ / T 73023-2006 standard; the nylon fibers were placed outdoors for 15 days, and the colors before and after the placement were tested using a colorimeter to obtain ΔE (ΔE is the color difference value, which characterizes the size of the color difference); the drip diffusion time of the nylon fibers was tested using the GB / T 21655.1-2023 standard; the test results are shown in Table 1:
[0051] Table 1
[0052]
[0053]
[0054] It can be seen from Table 1 that the nylon fibers prepared by melt spinning the antibacterial nylon chips prepared in Examples 1 to 4 have excellent antibacterial properties, discoloration resistance and hydrophilicity, which are better than those of Comparative Examples 1-2.
[0055] Comparison between Example 1 and Example 4 shows that the weight ratio of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG will affect the hydrophilicity of nylon fiber, because the change in the amount of adipic acid AA will affect the ratio of polyamide segments to polyether segments in the amino-terminated polyether molecule, thereby affecting the hydrophilicity of nylon fiber. The optimal weight ratio is 1.0:3:1.
[0056] Comparative Example 1 is compared with Example 1, which shows that the silver ion antibacterial agent obtained by amidated chitosan PMCS modified Ag nanoparticles overcomes the problems of unstable antibacterial performance of common silver ion antibacterial agents and easy discoloration of nylon fibers. Comparative Example 2 is compared with Example 1, and the hydrophilicity of nylon fibers is deteriorated.
[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an antibacterial nylon slice, characterized in that: Prepared by the following steps: S1, amidation modification of chitosan using methyl acrylate and amino-terminated polyether to obtain amidated chitosan PMCS; S2, using amidated chitosan PMCS to modify Ag nanoparticles to obtain silver ion-carrying antibacterial agent PMCS-Ag; S3, melt-blending the silver ion antibacterial agent PMCS-Ag with the nylon slices, and slicing them after cooling to obtain the antibacterial nylon slices.
2. The method for preparing an antibacterial nylon slice according to claim 1, characterized in that: The steps of amidation modification of chitosan using methyl acrylate and amino-terminated polyether in S1 are as follows: S11, chitosan and methyl acrylate undergo Michael addition reaction: chitosan powder is added to a methanol solution, and the mixture is continuously stirred until the chitosan powder is completely dispersed in the methanol solution; methyl acrylate is added to the solution, and the solution is stirred at 50-60° C. for 20-24 hours, and then centrifuged and washed to obtain a precipitate; S12, preparing amino-terminated polyether: mixing adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG, heating to 170-180° C. under N2 protection, and keeping warm for 30-60 min; adding an antioxidant phosphorous acid accounting for 2-3% of the total amount of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG, heating to 220-260° C. for polycondensation reaction for 1.5-3.5 h, thereby obtaining amino-terminated polyether; S13, the terminal ester group of chitosan undergoes an amidation reaction with the amino-terminated polyether: the precipitate in S11 is added to a methanol solution, and the stirring is continued until the precipitate is completely dispersed in the methanol solution; the amino-terminated polyether is added to the methanol solution, and the solution is stirred at 50-60° C. for 20-24 hours, and then centrifuged and washed to obtain amidated chitosan PMCS.
3. The method for preparing an antibacterial nylon slice according to claim 2, characterized in that: The dosage ratio of chitosan powder to methyl acrylate in S11 is 3-5 g: 0.5-1.0 mL.
4. The method for preparing an antibacterial nylon slice according to claim 2, characterized in that: The weight ratio of adipic acid AA, hexamethylenediamine HDA and double-terminated carboxyl polyethylene glycol CT-PEG in S12 is 0.6-1.2:3:1; The molecular weight of double-terminated carboxyl polyethylene glycol CT-PEG is 1000.
5. The method for preparing an antibacterial nylon slice according to claim 2, characterized in that: The ratio of the precipitate to the amino-terminated polyether in S13 is 3-5 g: 1-2 mL.
6. The method for preparing an antibacterial nylon slice according to claim 1, characterized in that: The steps of using amidated chitosan PMCS to modify Ag nanoparticles in S2 are: Take the amidated chitosan PMCS powder, add it to distilled water, and add glacial acetic acid to adjust the pH value to 3-4 to completely dissolve the PMCS; then add AgNO3 solution and stir to mix; then add the newly prepared NaBH4 solution dropwise, and stir to react for 10-15 minutes; add ammonia water to adjust the pH value to alkaline so that a precipitate appears in the solution, and the solution is centrifuged to obtain a solid substance. The solid substance is washed with distilled water, washed with acetone, and dried at room temperature for 10-12 hours to obtain a silver ion-loaded antibacterial agent PMCS-Ag.
7. The method for preparing an antibacterial nylon slice according to claim 6, characterized in that: The dosage ratio of PMCS, AgNO3 solution and NaBH4 solution is 0.05-0.1g:1-10mL:0.5-1mL; the concentration of AgNO3 solution is 10mmol / L, and the concentration of NaBH4 solution is 100mmol / L.
8. The method for preparing an antibacterial nylon slice according to claim 1, characterized in that: The silver ion antibacterial agent PMCS-Ag in S3 accounts for 1-10% of the mass of the nylon slice; The temperature of melt blending is 180-220°C.
9. An antibacterial nylon slice, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Cited By
Preparation method of semi-dull chinlon chips
CN121087638A
